RESONANCE-ENHANCED SUM-FREQUENCY GENERATION OF XUV RADIATION IN CO - Merkt, F; Softley, T (1990)
Resonance-enhanced sum-frequency generation of XUV radiation is observed for the first time in a molecular gas. Two laser frequencies are mixed in a pulsed free jet of carbon monoxide. The first laser is two-photon resonant with the Q-branch of the C1Σ+-X1Σ+ transition, while the second laser is tuned so that the sum frequency 2ν1 + ν2 is also resonant with various Rydberg state transitions in the range 107070-109310 cm-1. A spectrum is obtained by monitoring the sum-frequency intensity versus the frequency of the second laser. Rotational constants are obtained for four states and the intensity profiles show some remarkable effects of competition between four-wave mixing and reabsorption of the sum frequency. © 1990.